2013
DOI: 10.5488/cmp.16.31701
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and dielectric characterization studies on relaxor- and ferroelectric-like strontium-barium niobates

Abstract: Ferroelectric domain structure evolution induced by an external electric field was investigated by means of nematic liquid crystal (NLC) method in two strontium-barium niobate single crystals of nominal composition: Sr 0.70 Ba 0.30 Nb 2 O 6 (SBN:70 -relaxor) and Sr 0.26 Ba 0.74 Nb 2 O 6 (SBN:26 -ferroelectric). Our results provide evidence that the broad phase transition and frequency dispersion that are exhibited in SBN:70 crystal have a strong link to the configuration of ferroelectric microdomains. The larg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These conditions must be further investigated by e.g. in-situ real space domain mapping [9], [23], [57]. Thus, our results extend the list of possible connections between ferroic order and functional properties of materials.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…These conditions must be further investigated by e.g. in-situ real space domain mapping [9], [23], [57]. Thus, our results extend the list of possible connections between ferroic order and functional properties of materials.…”
mentioning
confidence: 81%
“…We have chosen SBN50 as a model uniaxial ferroelectric whose para-and ferroelectric phases are tetragonal (c/a ~ 0.31 e.g. [21]), formation of ferroelastic domains is forbidden and static patterns of purely ferroelectric domains are well documented [22][23][24]. We quantified the electric-field induced strain and demonstrated that the volumes of rapid domain growth / merging during the polarization reversal exhibit anomalously high deformation under electric field (~400 pC/N), comparable to that of the PZT [25,26].…”
mentioning
confidence: 99%
“…In particular, dependences of the switch ing parameters on the composition and method of fab rication of the film [4], the influence of size effects on the switching parameters, and the influence of param eters of the variable electric field [5][6][7] are being stud ied. These parameters are critically important for studying the feasibility of devices based on low dimensional ferroelectric structures.…”
Section: Introductionmentioning
confidence: 99%